Tinjauan Sistematis Tantangan dan Peluang Implementasi Model Pembiayaan Pendidikan Berbasis Human Capital untuk Pembangunan Sumber Daya Manusia Unggul di Indonesia - Ambrosius Tode Peya Nia Do; Masduki Ahmad; Heni Rochimah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The development of superior Human Resources (HR) is an essential prerequisite for a nation's progress. In the Indonesian context, education financing based on human capital, as a form of investment in HR, is a strategic step that requires comprehensive review from both opportunity and challenge perspectives. This research aims to conduct a systematic review of the literature related to the challenges and opportunities of implementing a human capital-based education financing model within the Indonesian education context, as well as its contribution to the development of superior HR. Furthermore, this research will formulate policy recommendations derived from the analysis and identify relevant research gaps. Through a Systematic Literature Review (SLR) approach, this study explores critical issues such as financing standards, optimization of fund allocation, education budget management, and accountability and equity challenges. The analysis results indicate strong recognition of education as a